The Effect of Prolonged Feeding of Stylosanthes guyanensis Meal on Laying Performance, Egg Quality and Hatchability - Onwudike, O. C.; Adegbola, A. A. (Faculty of Agriculture, University of Ife, 2015)
The utilization of increasing levels of Stylosanthes guyanensis meal (stylo meal) by laying chickens feed for a period of nine months and the effect of increasing levels of vitamin A on the hatchability of eggs were studied using Single Comb White Leghorn birds. The feeding of stylo meal to laying birds lengthened the time taken by the birds to get to peak production. There was no significant effect on the average hen-day production percentage following the feeding of up to 20% stylo meal. The control diet in which there was no stylo meal however had a better production rate than any of the other diets. The feeding of stylo meal increased egg riboflavin content, egg hatchability and yold cholesterol level and depressed serum cholesterol level. The improved egg hatchability observed in this study could not be related entirely to the improved vitamin A status of the diets with the addition of stylo meal. It is suggested that the utilization of higher levels of stylo meal could be improved by a better amino acid balance and pelleting of the rations.